Galloyl benzamide-based compounds modulating tumour necrosis factor α-stimulated c-Jun N-terminal kinase and p38 mitogen-activated protein kinase signalling pathways. (16th June 2015) - Leo, Valentina; Stefanachi, Angela; Nacci, Carmela; Leonetti, Francesco; de Candia, Modesto; Carotti, Angelo; Altomare, Cosimo D; Montagnani, Monica; Cellamare, Saverio
Abstract: Objectives: The aim of this work is to investigate whether and how two newly synthesized 3, 4, 5-trimethoxygalloyl-containing compounds 1 and 3 interfere with the mitogen-activated protein kinase (MAPK) signalling pathways involved in several pathological events, ranging from inflammatory diseases to cancer. Methods: The effects on the phosphorylation of MAP kinases (c-Jun N-terminal kinases (JNKs), p38) and activation of nuclear factor-kappa B (NF-κB) pathways of 1 and its 1 H -indazole-containing analogue 3, compared with those elicited by the known Adenosine Triphosphate (ATP)-competitive JNK inhibitor SP600125, were evaluated through Western blot analysis in murine fibroblasts NIH-3T3 and human endothelial cells EA.hy926 acutely treated with tumour necrosis factor-α (TNF-α). Their effects on cell viability were also assessed by 3-[4, 5-dimethylthiazol-2-yl]-2, 5-diphenyltetrazolium bromide (MTT) assay. Key findings: In cultured murine fibroblasts, 1 inhibited JNK signalling with a different mechanism from SP600125. It reduced c-Jun phosphorylation without altering phosphorylation levels of JNK protein. Compound 3, showing a profile similar to SP600125, inhibited JNK phosphorylation and partially inhibited p38 MAPK at 50 μm concentration. Compound 3 and SP600125 showed similar behaviour in both cell cultures. In contrast, compound 1 in EA.hy926 cells significantly interfered with JNK phosphorylation, did not decrease phosphorylation of c-Jun (Ser73), whereas significantly suppressed phosphorylation of p38 MAPK and reversed degradation of NF-κB signalling components. Conclusions: 3, 4, 5-Trimethoxygalloyl-based compounds 1 and 3, which did not show significant cell toxicity, modulate the TNF-α-induced activation of MAPK signalling, mainly inhibiting phosphorylation of JNK, c-Jun and p38 MAPK, in murine fibroblasts and human endothelial cells with different MAPK selectivity profiles. These compounds deserve future investigation in specific cell-based disease models and in-vivo pharmacology.